Analysis of Code Mixing on Media Social Shopee - Cut Nur Mariska; Yusni Khairul Amri (Britain International for Academic Research (BIAR-Publisher), 2022)
The purpose of this study is to identify and describe external code mixing, internal code mixing and mixed code mixing on shopee social media. This study uses the theory of Sayama Malabar, Chaer and Agustina, Padmadewi et al, Nababan and Suardi. The method used in this study is a qualitative method using an analysis of the use of code mixing on shopee social media. The data analysis technique is used by learning about code mixing on Shopee's social media, studying the words found on Shopee's social media, concluding the results of the analysis. This research instrument is used to record code mixing on shopee social media. The results of this study obtained 50 code-mixed data, there were mixed code inside 5 with all 10 words, outside code mixed 40 with all words 840, and mixed code mixed 5 with all 91 words.